Effects of three different diets on the fatty acid profile and sensory properties of fresh Pecorino cheese “Primo Sale” - Isa Fusaro (Asian-Australasian Journal of Animal Sciences, 2020)
Objective This study aimed to evaluate and compare the effects of three different diets on the fatty acids (FA) profile and sensory properties of a characteristic Italian fresh cheese: Pecorino “Primo Sale” (PS). Methods Fifty-four sheep were divided into three feeding groups: total mixed ration (TMR) enriched with extruded linseed (TL), control diet with TMR without any integration (TC), and pasture (P). During cheese production, six cheeses per experimental group were produced each week, stored for 10 days at 4°C, and then analyzed for chemical composition, FA profile, and sensory properties. Results Saturated fatty acids (SFA) were significantly higher in PS from group TC (82.11%) than in cheese from other two groups (P 75.48% and TL 66.83%). TL and P groups presented higher values of polyunsaturated fatty acids, 4.35 and 3.65%, respectively, than that of TC group (2.31%). The lowest SFA/unsaturated fatty acid ratio was found in TL and P groups, while the highest was found in the TC group. Vaccenic acid and conjugated linoleic acid (CLA) were higher in group P (p<0.05) than in groups L and TC. Sensory properties of cheese from group P received the highest scores for odor intensity and friability, while control group had a greater chewing consistency. Overall, all cheeses received good scores for acceptability. Conclusion In conclusion, this study showed how the integration of extruded linseed improved the FA profile of fresh pecorino cheese PS preserving its sensory properties. Levels of CLA in the PS group achieved using this approach was not higher than that in a grazing diet. Cheeses from groups P and L contained a higher value of FA, with nutritional implications for humans, when compared with un-supplemented diet. Linseed may be a good feeding strategy when pasture is not available.